The influence of power of tax administrator on cognitive and affective tax attitude in Malaysia - Siti Fatimah Abdul Rashid,; Rosiati Ramli,; Mohd Rizal Palil,; Amizawati Mohd Amir, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article offers insights into the influence of the tax administrator’s power on individual taxpayers’ cognitive and affective (emotion) attitudes in Malaysia. This article applies a quantitative approach using surveyed questionnaires on professional taxpayers in Malaysia. A structural equation model (SEM) using AMOS is employed in the data analysis. Two relationships are reported as insignificant concerning legitimate foundation power with cognitive capitulation and affective capitulation. The remaining hypothesised relationships are found significant. First, both cognitive resistance and affective resistance attitude are influenced positively by coercive power. Second, both cognitive capitulation and affective capitulation attitudes are influenced positively by persuasive power and reward power. Third, cognitive and affective commitment are influenced negatively by coercive power and positively by the legitimate foundation and reward power. This article argues that the tax administrator’s power influences both cognitive attitude and emotion, which means a comparable effect was found on cognitive and affective attitudes. However, harsh power through enforcement has a greater influence on cognitive defiance attitude than negative emotion. Similarly, the influence of coercive power (negatively), legitimate foundation and reward power is seen more on cognitive deference attitude than their influence on taxpayers’ deference emotion. In contrast, using the soft power of persuasive and reward power has more effect on taxpayers’ deference emotions than cognitive deference. The results suggest that tax administrators implement a targeted approach in their compliance strategies depending on taxpayers’ attitudes. This targeted approach could yield the highest compliance level using the minimum resources possible.